Inhibition of chymotrypsin by heparin cofactor II. - Church, F C (1985)
Human heparin cofactor II is a plasma protein that is known to inhibit thrombin. The rate of thrombin inhibition by heparin cofactor II is accelerated (greater than or equal to 1000-fold) in the presence of the glycosaminoglycans, heparin and dermatan sulfate. We have found that chymotrypsin A alpha is also inhibited by heparin cofactor II with a second-order rate constant value of 1.8 X 10(6) M-1 X min-1 at pH 8.0 and 25 degrees C. However, there was no measurable effect of heparin or dermatan sulfate on the rate of chymotrypsin inhibition. Arginine-modified heparin cofactor II showed a comparable percentage loss of both antichymotrypsin and antithrombin activities. Heparin cofactor II and chymotrypsin formed a stable complex with a Mr value near 90,000 when analyzed by NaDodSO4/polyacrylamide gel electrophoresis; this suggests a 1:1 reaction stoichiometry. The chymotrypsin cleavage site in heparin cofactor II was the same as that for thrombin, and primary structure analysis of the inhibitor showed a P'1-P'8 sequence of Ser-Thr-Gln-Val-Arg-Phe-Thr-Val ... . The results indicate that, in contrast to alpha 1-antichymotrypsin, which does not inhibit trypsin-like enzymes, including thrombin, heparin cofactor II can effectively inhibit both thrombin and chymotrypsin.